Modulation of High-Density Lipoprotein Function via Cardiac Rehabilitation - Ishida, Tatsuro; Satomi-Kobayashi, Seimi (Journal of Atherosclerosis and Thrombosis, 2018)
[See article vol. 25: 153-169] Currently, cardiac rehabilitation (CR) is regarded as one of the most important and indispensable therapies for coronary artery disease (CAD). The effect of CR on the secondary prevention of CAD was established in meta-analyses in terms of improving total mortality, hospitalization rate, exercise capacity, and quality of life. Additionally, a large number of studies support the ameliorating effects of CR on coronary risk factors, such as hypertension, impaired glucose tolerance, and dyslipidemia. CR was reported to increase the high-density lipoprotein cholesterol (HDL-C) level and decrease the triglyceride level. However, the mechanism underlying the beneficial effect of CR has been insufficiently understood. In particular, it is unclear whether CR can modulate the lipoprotein quality. Although there are a certain number of studies investigating the effects of CR on the HDL function, the clinical effects remain controversial. The most plausible reason for inconsistent results in previous studies could possibly be attributed to the small sample size, probably because a number of participants had issues in completing the CR programs.